Stelian Pașca-Tușa, Bogdan Șopterean (eds.), „Studii biblice in honorem Pr. prof. univ. dr. Ioan Chirilă” [“Biblical Studies in honorem Rev. Prof. Ioan Chirilă, PhD”] (Cluj-Napoca: Presa Universitară Clujeană, 2023), 455 p. - ȘTEFAN, Cătălin-Emanuel (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2023)
Homage volumes, following the model of the long-established Western ones, are no longer a novelty. It has long been accepted that almost every university professor will have at least one memorial volume dedicated to him or her on reaching the 'round' age of 60, 65, 70 or more. These volumes comprise a series of studies conducted by other academics, sometimes with a central theme and sometimes leaving the authors free to tackle any subject they wish. At the end of these studies, a personal message of congratulations and admiration for the academic personality to whom the volume is dedicated appears. The volumes are also prefaced by a substantial introduction which outlines the portrait of the person being honoured and their work and contribution to scientific research. So, this kind of academic literature has a precise 'recipe'.